The Dependence of Iraqi Radio Stations on Social Media Applications as a Source of Information: A Field Study - Jaafar, Basim Ahmed; Al Kaabi, Raad Jasim (ALBAHITH ALALAMI, 2025)
Objectives: This study aims to determine the extent to which Iraqi radio professionals rely on social media platforms as sources of information, identify the most widely used platforms among media personnel, assess the perceived credibility of content published on these platforms, and measure the level of trust in information that includes audio or visual content shared through social media.Methodology: The study adopted a descriptive-analytical methodology, specifically using a field survey approach through a questionnaire designed to meet the research objectives. Additionally, personal interviews were conducted with a purposive sample of 100 communication professionals working in the newsrooms of six major Iraqi radio stations. Data were collected from December 27, 2022, to February 13, 2023, considering the geographical, temporal, and functional distribution of the respondents.Results: The results indicated that Iraqi radio professionals rely moderately on social media as an information source. Telegram ranked first among the most used platforms due to its publishing freedom and ease of video sharing, especially in covering breaking news. Respondents preferred information accompanied by visual or audio content to enhance trust and credibility. Levels of trust varied across platforms, with WhatsApp gaining the highest trust, while Viber ranked lowest.Conclusion: The study confirms that social media has become a primary information source for Iraqi radio stations in the age of digital media. However, professional use of these platforms still requires caution, particularly regarding the verification of content accuracy. The study recommends enhancing digital verification skills among journalists and updating editorial policies to effectively integrate traditional and digital sources.